PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS PUISI RAKYAT SISWA KELAS VII SMP NEGERI 6 KOTA JAMBI TAHUN AJARAN 2017/2018 - Nirma Yanti; Abdoel Gafar; Afif Rofii (Universitas Batanghari, 2018)
This research is aimed at identifying the use of picture media towards students class VII in writing foelk poetry in SMP Negeri 6 Kota Jambi. This research is quasi experiment. There are two classes used in this research, they are class VII A which consists of 35 students as control class and class VII B consists of 34 students as experiment class. Normality test, homogenity test are used in counting the mean of the result. Hte result of normality test from control class is Lcount = 0,9534 and in experiment class Lcount = 0,9629, while homogenity test is 1,38 and the test similiraity shows 0,162 bigger than significat  = 0,05. It means that this research is homogen and falls into the same condition. The result of the research shows that the value of tcount =2,164 bigger that ttable= 1,99601with significant  = 0,05 with dk 67. It can be concluded that picture media has a significant effect towards students class VII in writing foelk poetry in SMP Negeri 6 Kota Jambi.Key Word : picture media, writing foelk poetry